The comparative effects of manganese nanoparticles and their counterparts (bulk and ionic) in Artemisia annua plants via seed priming and foliar application - Salehi, Hajar; Cheheregani Rad, Abdolkarim; Raza, Ali; Djalovic, Ivica; Prasad, P. V. Vara (Frontiers in Plant Science, 2023)
The world has experienced an unprecedented boom in nanotechnology. Nanoparticles (NPs) are likely to act as biostimulants in various plants due to having high surface/volume value. However, understanding the actual effect of NPs is essential to discriminate them from other counterparts in terms of being applicable, safe and cost-effective. This study aimed to assay the impact of manganese(III) oxide (Mn2O3)-NPs via seed-priming (SP) and a combination of SP and foliar application (SP+F) on Artemisia. annua performance at several times intervals and comparison with other available Mn forms. Our findings indicate that SP with MnSO4 and Mn2O3-NPs stimulates the processes that occur prior to germination and thus reduces the time for radicle emergence. In both applications (i.e., SP and +F), none of the Mn treatments did show adverse phytotoxic on A. annua growth at morpho-physio and biochemical levels except for Mn2O3, which delayed germination and further plant growth, subsequently. Besides, from physio-biochemical data, it can be inferred that the general mechanism mode of action of Mn is mainly attributed to induce the photosynthetic processes, stimulate the SOD activity, and up-regulation of proline and phenolic compounds. Therefore, our results showed that both enzymatic and non-enzymatic antioxidants could be influenced by the application of Mn treatments in a type-dependent manner. In general, this study revealed that Mn2O3-NPs at the tested condition could be used as biostimulants to improve germination, seedling development and further plant growth. Still, they are not as effective as MnSO4 treatments. Still, these findings could be useful in considering and developing Mn2O3-NPs-priming in future studies to improve seed germination and seedling quality of plants.